The Digital Transformation of India - A Case Study of Accelerated Mobile Internet - Pratiksha Ashok (International Telecommunications Society (ITS), 2023)
India- the land where tradition meets modernization, where local meets global, a land that has changed its image from an agrarian world to an equal competitor in the digital sector, a society where digitalization has not ripped traditional roots but uplifted small businesses and budding entrepreneurs. In 2016, 16.5% (214.5 million) of the Indian population had access to mobile internet. In 2017, 18.2% of Indians (236 million) had access to mobile internet, an increase of approximately 22 million people having access to mobile internet in a year. The Indian Telecom Sector has emerged as one of the critical components of economic growth required for overall socio-economic development of the country as there is a positive correlation between the penetration of mobile services and internet on the growth of GDP of a country. So, what are changed in 2016, contributing to the acceleration of mobile internet usage in India? The various factors that contributed and the impact on the consumers are the focus of this research. The factors include the rise of mobile service providers, digitalization, government policies and COVID-19, resulting in increased healthy competition, access to infrastructure and subsidies, a secure financial system and resilience in the face of a global health crisis. (...)
Keywords: 330